The Use of Code-Switching in English as A Foreign Language Classrooms in Teacher’s Perspective - Suryarini, Diah Yovita (Universitas Pahlawan Tuanku Tambusai, 2022)
The practice of code switching still become a debatable notion between researchers, is it detrimental as a sign of a teacher’s lack of competence or beneficial as a communication strategy in English teaching learning process, Despite the controversy on code switching among researchers, teachers still practice it in their EFL classroom. The purpose of this study was to investigate teacher’s perspective in maintaining the use of code-switching in their EFL classroom as an instructional strategy. This study uses qualitative descriptive method. The data was collected primarily from interviews from five English teachers. The result showed that the teacher practiced the code switching because the institution allowed the code switching practice in the classroom However, teachers limited the use of code switching only when they should explain the language rules, and when the teachers gave task instruction so that the student did not misunderstand the instruction. Teachers believe that code switching support them in instructional and managerial matter in EFL class and they used code-switching as little as possible and usually in their beginner class. The teachers believed that using code switching can serve pedagogical purpose and communication strategy in their EFL classroom.